ANALISIS LAYANAN BIMBINGAN BELAJAR DI TAMAN ILMU DESA MEKAR JAYA KECAMATAN BUNGURAN BARAT KABUPATEN NATUNA - Syah, Hardian; Salim, Izhar; Hidayah, Riama Al (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to study learning guidance service at Taman Ilmu, Desa Mekar Jaya. The research used problem in this research was how is learning guidance performed and the hampered. This research used qualitative research with descriptive method. The technique to collect the data on this research were observation, interview and documentations. The procedure of data analysis was data reduction, data presentation and verification. To validity the data used the lest to include the triangulation technique in the similar data but difference technique. The result of this research was that learning guidance service, the supervisor did identify the problem of learning students’ faced from attitude and habitual. To solve the problem, the supervisor in problem of learning gave instruction to explained the purpose of the delightful learning situation between teacher with the student and the student with the student. There are some hampered supervisors’ faced, limited to explain about learning guidance, limited the facility for example, the reading book, and difficult to combined between learning method with the learning guidance method. Keywords : Analysis, Learning Guidance Service, Taman Baca Masyarakat